2021
DOI: 10.1111/rec.13577
|View full text |Cite
|
Sign up to set email alerts
|

Using demographic findings to compare wild and translocated populations of Florida goldenaster (Chrysopsis floridana) in west‐central Florida, U.S.A.

Abstract: Evaluation of the success of rare plant introductions requires analysis of demographic success. We analyze the success of 10 wild and 8 introduced populations of Florida goldenaster (Chrysopsis floridana), a federally endangered forb endemic to west‐central Florida, using demographic and stage‐class data collected from 2017 to 2019. We also collected microhabitat data to characterize factors associated with this species' success. Introductions had higher annual survival rates and fecundity than wild population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…(Menges et al, 2008;Menges et al, 2017). By selecting what we considered to be "preferred habitats," we were able to select favorable micro-sites that may have contributed to our early success (Halsey et al, 2017;Ward et al, 2021;Wendelberger & Maschinski, 2016). In addition, the use of healthy plants and initial supplemental water may have increased vital rates in translocations relative to wild populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Menges et al, 2008;Menges et al, 2017). By selecting what we considered to be "preferred habitats," we were able to select favorable micro-sites that may have contributed to our early success (Halsey et al, 2017;Ward et al, 2021;Wendelberger & Maschinski, 2016). In addition, the use of healthy plants and initial supplemental water may have increased vital rates in translocations relative to wild populations.…”
Section: Discussionmentioning
confidence: 99%
“…Based on observations of wild D. christmanii and other Florida scrub congeners (Evans et al, 2008, 2010; Menges et al, 2006; Menges et al, 2019; Peterson et al, 2013), we know their preferred habitat is open gaps, and larger gaps sustain greater abundances (Menges et al, 2008; Menges et al, 2017). By selecting what we considered to be “preferred habitats,” we were able to select favorable micro‐sites that may have contributed to our early success (Halsey et al, 2017; Ward et al, 2021; Wendelberger & Maschinski, 2016). In addition, the use of healthy plants and initial supplemental water may have increased vital rates in translocations relative to wild populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the scrub and roadsides did not significantly differ in their numbers of viable seeds or aboveground plants for Papery Whitlow-wort, roadsides did have fewer viable seeds and more plants than the scrub, suggesting the same higher germination, recruitment, or survival rate may be at play here. As previously discussed, studies have shown that scrub plants survive at reduced rates on roadsides compared to the scrub (Schafer et al 2013, Ward et al 2022; therefore, we believe that high roadside germination or recruitment rates followed by high mortality is a likely explanation for similar numbers of adult plants in scrub and on roadsides.…”
Section: Discussionmentioning
confidence: 53%
“…There are no studies, to our knowledge, that examine unpaved roads' effect on seed viability, but we provide some hypotheses here. In the Florida scrub, roadside plants survive at lower rates than those in interior habitat (e.g., Schafer et al 2013, Ward et al 2022) so may devote fewer resources to seed production and produce lower-quality seeds. Alternatively, a reduction in seed viability may stem from seeds degrading in the soil or edaphic conditions preventing the germination of viable seeds or perhaps inducing seed dormancy, but more research is needed to form any conclusions.…”
Section: Discussionmentioning
confidence: 99%